NAQSHBANDI SPIRITUALITY AND THE DIGITAL AGE: A CONCEPTUAL RESPONSE TO SOCIAL MEDIA–RELATED MORAL CHALLENGES - Ali Muhammad Bhat; Ahmad Munir (QAULAN: Journal of Islamic Communication, 2025)
This article examines how Naqshbandi Sufi principles can serve as a spiritual framework for addressing the ethical and psychological harms associated with contemporary social media culture. The study employs a conceptual and hermeneutic textual analysis, using classical Naqshbandi treatises and Qur’anic–Prophetic teachings as primary sources. These texts were thematically analyzed to extract the Eleven Naqshbandi Principles and map them to major digital harms documented in media psychology literature, such as addiction, distraction, narcissistic self-presentation, cyberbullying, and exposure to harmful content. The article proposes a theoretical model the Naqshbandi Digital Ethics Framework which integrates attention discipline, intention purification, and moral self-regulation as spiritual countermeasures to these harms. The findings contribute to Islamic communication ethics and offer practical implications for da‘wah, education, and digital literacy initiatives. The article further outlines directions for future empirical validation through educational and counseling interventions.